Oral glucose tolerance test: unnecessary requests and suitable conditions for the test - Gabriele A. Silva; Cláudio L. Souza; Márcio V. Oliveira
ABSTRACT Introduction: The oral glucose tolerance test (OGTT) is an important test for diagnosis of diabetes mellitus (DM) that needs criteria to be requested and analytical performance evaluation. Objectives: Determine the prevalence of unnecessary OGTT requests and analyze patients' suitability criteria for glucose load. Method: Cross-sectional, descriptive and analytical study conducted with 554 patients who had OGTT requested from January to April 2018. Data from laboratory tests were collected through Complab Advanced version 6.9.6 system, organized into a Microsoft® Excel table and analyzed using Epi InfoTM, version 7.2.1.0. The accuracy of the glucometer paired analysis was performed by determinations of Student's t test, using SPSS version of IBM 21TM. Patients with a previous diagnosis of DM and/or who showed OGTT request as a screening test along with blood glucose or glycated hemoglobin were classified as unnecessary requests. Results: Among the studied patients, 17% (94) had unnecessary OGTT requests, 53 (53.4%) patients had blood glucose ≥ 140 mg/dl and previous DM and/or OGTT used as screening; 41 (43.6 %) patients with capillary blood glucose < 140 mg/dl, but with a diagnosis of DM. The glucometer proved to be accurate with a high correlation (r 2 = 0.97, p < 0.0001) with serum glucose. Approaches during screening and capillary blood glucose prevented unnecessary exposure to glucose overload in 67% (63) of the patients. Conclusion: The high prevalence of unnecessary OGTT requests underscores the need of criteria for OGTT requesting and the standardization of procedures for screening in the exam.